Some special features of the water regime and the photosynthetic apparatus functioning in garden roses under drought conditions - R. A. Pilkevich; S. A. Plugatar; T. B. Gubanova (Труды по прикладной ботанике, генетике и селекции, 2025)
Data are presented on changes in the total water content in leaf tissues and the level of real water deficiency in 7 genotypes of garden roses (Rosa gallica L., R. odorata var. gigantea × R. multiflora, R. hugonis Hemsl., R. chinensis var. minima (Sims) Voss., R. bracteata J.C. Wendl., and R. foetida var. persiana (Lem.) Rehder) and cv. ‘Borisfen’ during the summer seasons of 2022–2023 on the Southern Coast of Crimea. Most genotypes showed a sublethal limit of water deficiency with the loss of 22–26% of water in their leaves. The leaf water regime was described for the studied genotypes under the extreme drought of 2023. For R. gallica, the critical limit of water loss was 10–15%. Simulating conditions close to the hot dry wind (t = 27°C, Rh = 30%) resulted in a more intensive loss of moisture by the leaves of the studied roses, while only R. odorata var. gigantea × R. multiflora showed a reduction in water consumption. The threshold for sublethal moisture deficiency in the leaves of relatively resistant plants (cv. ‘Borisfen’ and R. hugonis) dropped to 20–24%.Analyzing main parameters of chlorophyll fluorescence induction proved that the development of water deficiency in the range of 20–25% under low air humidity caused an irreversible inactivation of PS II in R. bracteata, R. gallica, and R. odorata var. gigantea × R. multiflora. Disturbances in the functioning of the photosynthetic apparatus in cv. ‘Borisfen’, R. hugonis, and R. foetida var. persiana were reversible. The variable fluorescence level and the fluorescence decay rate are informative for determining the degree of drought resistance in garden rose plants.